1998
DOI: 10.1093/rheumatology/37.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin antibodies in giant cell arteritis and polymyalgia rheumatica: a study of 40 cases

Abstract: The occurrence and clinical value of anticardiolipin antibodies (aCL) were studied in 33 patients with giant cell arteritis (GCA) and in seven patients with polymyalgia rheumatica (PMR), at onset and during follow-up. aCL were present in 19/40 (47.5%) GCA/PMR cases, most of them of the IgG isotype, whereas all controls (21 subjects) were aCL negative. The presence of aCL was not associated with inflammatory parameters or clinical signs of arteritis; however, they disappeared in a significant percentage (56%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 0 publications
0
18
0
2
Order By: Relevance
“…It has been suggested that anticardiolipin antibodies present in these situations were an epiphenomenon of exposed endothelial cells and did not have prothrombotic properties. 18,19 This could explain why 2 of the present patients who initially tested negative for antiphospholipids had low positive titers on repeated testing months later. The pathogenicity of the antibodies may also be affected by host genetic factors, antibody isotype, and vessel wall integrity.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…It has been suggested that anticardiolipin antibodies present in these situations were an epiphenomenon of exposed endothelial cells and did not have prothrombotic properties. 18,19 This could explain why 2 of the present patients who initially tested negative for antiphospholipids had low positive titers on repeated testing months later. The pathogenicity of the antibodies may also be affected by host genetic factors, antibody isotype, and vessel wall integrity.…”
mentioning
confidence: 81%
“…Antiphospholipid antibodies have also been positive for disease in a variety of primary systemic vasculitides, including Wegener granulomatosis, giant cell arteritis, polyarteritis nodosa, and Churg-Strauss syndrome. [18][19][20][21][22] In a recent study,…”
Section: Commentmentioning
confidence: 99%
“…Témoignant du possible rôle de l'immunité humorale, la présence de différents types d'auto-anticorps a été rapportée au cours de la MH mais sans que leurs rôles pathogéniques soient clairement démontrés. Ainsi, des anticorps anti-cardiolipines (aCL) ont été détectés chez 20 à 50 % des patients affectés de MH, mais à taux faible, sans anticorps anti-b2glycoprotéine I et sans association avec une augmentation du risque ischémique [65][66][67][68][69]. Ces aCL disparaissent après 3 mois de corticothérapie [69,70].…”
Section: Rôle De La Réponse Immunitaire Humoraleunclassified
“…Ainsi, des anticorps anti-cardiolipines (aCL) ont été détectés chez 20 à 50 % des patients affectés de MH, mais à taux faible, sans anticorps anti-b2glycoprotéine I et sans association avec une augmentation du risque ischémique [65][66][67][68][69]. Ces aCL disparaissent après 3 mois de corticothérapie [69,70]. Des anticorps anti-cellules endothéliales (aCE) ont été détectés chez 33 % des patients atteints de MH [71].…”
Section: Rôle De La Réponse Immunitaire Humoraleunclassified
“…Since autoantibodies [23], in particular anticardiolipin antibodies [24,25], have also been proposed to play a role in the clinical spectrum of manifestations of GCA, in the current study we sought to investigate the potential association of the C8orf13-BLK region with susceptibility to biopsy-proven GCA, We also assessed whether polymorphisms in this region might influence the clinical spectrum of manifestations of this systemic vasculitis. For this purpose, we selected the rs13277113 and rs2736340 variants of the C8orf13-BLK gene region, as they were found to be the C8orf13-BLK gene variants most strongly associated with susceptibility to SLE [13], and as these gene variants were associated with alterations in B-cell receptor signaling and NF-B signaling pathways [26].…”
Section: Introductionmentioning
confidence: 99%